Pendampingan Pembangunan Tugu Batas Desa Bagoang Kecamatan Jasinga Kabupaten Bogor - Dede Permana; Neng Hodijatul Kubro; Andreas Seantanu; Mohamad Najib; Utamy Sukmayu Saputri (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2023)
Thematic real work lecture is a form of implementation of the higher education in which it provides real work experience and learning for students in the implementation of community service and empowerment. Thematic real work lecture activities are a golden opportunity for students to be more critical, innovative, active, and creative in finding the right solutions, formulations and strategies in solving problems and developing in the village. Development is often interpreted as meeting the needs of physical facilities and infrastructure imported from outside, carried out with a very dominant government role and with top-down planning. Likewise with village and rural development, which at the location Bagoang village, initially there was a village boundary monument, but due to building maintenance that was never paid attention to and factors from the age of the building itself which was quite old, causing the monument to collapse and reach currently no new village boundary monument has been made, so based on the consideration of our group, we intend to do community service by making building plans and constructing boundary monuments in Bagoang Village.